Unspoken words: decoding the dialog between type 2 innate lymphoid cells and T cells - Ikra, Zahra Jamila; Huang, Qiutong; Yu, Huiyang; Belz, Gabrielle T.; Jenne, Craig N.; Jacquelot, Nicolas (Frontiers in Immunology, 2025)
Type 2 innate lymphoid cells (ILC2s) are critical mediators of type 2 immunity that play non-redundant context-dependent modulatory functions. Primarily associated with responses against helminths and allergens via the activation of a potent epithelial-ILC2 axis, a growing body of evidence also suggests that a crosstalk between ILC2 and T cells is equally important in maintaining tissue homeostasis. In barrier tissues and secondary lymphoid organs, ILC2s co-localize with T cells, forming hubs where bi-directional signals are exchanged. Here, we describe the diversity of functional interactions between ILC2s and T cells, detailing known contact-dependent and -independent mechanisms, including a relatively new and still poorly defined antigen-presenting function during inflammation. Understanding these complex interactions is necessary to fully elucidate how this specific crosstalk helps maintain tissue homeostasis and regulate inflammatory responses. Identifying the spatial and temporal specificities of these interactions will certainly open new avenues for future targeting of this axis to improve immune-mediated host protection.